PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DI MADRASAH TSANAWIYAH NEGERI 1 BANDAR LAMPUNG - Sahit, Ahmad; Adib, Abdul; Widiastuti, Nur (UNISAN JURNAL, 2023)
The purpose of this study was to determine the stages of curriculum development in MTs N 1 Bandar Lampung. This study uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used was observation, interview and documentation techniques. This participatory observation technique was carried out to observe the geographic location in the form of a location plan and environmental conditions, vision, mission, strategy and motto of the school as well as the condition of human resources at MTs N 1 Bandar Lampung. Interviews were conducted to determine the stages of curriculum development. Based on the results of the proper description, the curriculum development management process cannot be separated from Team Work (cooperation) with the help of supporting resources. Implementation with a certain strategy that is effective and efficient, and refers to the vision, mission and goals that have been determined previously. The parties that play a role in the formation of the curriculum are the government, the school, the education bureau, the school committee. As for the problems in curriculum development management, there are the quality of the teachers themselves, school principals and school administrators, education supervisors (boards), school committees. These various kinds of problems, the role of a leader in overcoming existing problems is to always evaluate the performance of existing officials to further make improvements and improvements